2017
DOI: 10.1039/c6pp00298f
|View full text |Cite
|
Sign up to set email alerts
|

Singlet oxygen feedback delayed fluorescence of protoporphyrin IX in organic solutions

Abstract: Delayed fluorescence (DF) of protoporphyrin IX (PpIX) has been recently proposed as a tool for monitoring of mitochondrial oxygen tension in vivo as well as for observation of the effectiveness of photodynamic therapy (PDT) [E. G. Mik, Anesth. Analg., 2013, 117, 834-346; F. Piffaretti et al., J. Biomed. Opt., 2012, 17, 115007]. However, the efficiency of the mechanism of thermal activation (E-type DF), which was considered in the papers, is limited due to a large energy gap between the first excited singlet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 50 publications
0
21
0
1
Order By: Relevance
“…For the interpretation of the signal in terms of quantitative oxygen measurements additional research into the localization of PpIX and the photo‐physical properties of the delayed fluorescence would be very helpful. For example, Vinklárek et al described a Singlet Oxygen Feedback‐Induced mechanism (SOFDF) that influences the delayed fluorescence of PpIX under certain non‐physiological circumstances . It is currently unknown to what extent other mechanisms than T‐type delayed fluorescence, like this SOFDF mechanism, contribute to the in vivo delayed fluorescence signal.…”
Section: Discussionmentioning
confidence: 99%
“…For the interpretation of the signal in terms of quantitative oxygen measurements additional research into the localization of PpIX and the photo‐physical properties of the delayed fluorescence would be very helpful. For example, Vinklárek et al described a Singlet Oxygen Feedback‐Induced mechanism (SOFDF) that influences the delayed fluorescence of PpIX under certain non‐physiological circumstances . It is currently unknown to what extent other mechanisms than T‐type delayed fluorescence, like this SOFDF mechanism, contribute to the in vivo delayed fluorescence signal.…”
Section: Discussionmentioning
confidence: 99%
“…Although SOFDF cannot be applied to all photosensitizers, it was reported that a wide range of other photosensitizers are also capable of SOFDF emission (TPPS 4 , TMPyP, porphycenes, eosin, rose Bengal, etc. ), 20,26 including protoporphyrin IX, 27 which is currently the most frequently used photosensitizer in clinical PDT (it is formed endogenously in cells after administration of δ-aminolevulinic acid). Therefore, SOFDF-based singlet oxygen sensing could be potentially performed with a wide range of photosensitizers.…”
Section: Interpretation Of Singlet Oxygen Feedback Delayed Fluorescenmentioning
confidence: 99%
“…14 Recently, we proposed a completely different approach to monitoring singlet oxygen. [20][21][22] It is based on the mechanism of singlet oxygen feedback delayed fluorescence (SOFDF), [23][24][25] which is intrinsic to a number of different photosensitizers (protoporphyrin IX, ionic porphyrins, porphycenes, eosin, Rose Bengal, and others), 20,[26][27][28] and hence no additional probe molecule is required. The triplet state of a photosensitizer (T 1 ) can interact with the previously generated 1 O 2 , which leads to a reverse intersystem crossing (RISC) of the photosensitizer molecule and repopulation of the S 1 state that can subsequently emit a photon.…”
Section: Introductionmentioning
confidence: 99%
“…The thermDF is first order in the concentration of excited states, while the TTADF and SOFDF are second order, which makes their individual contributions dependent on the concentration of triplet states, which, itself, depends on the photosensitizer concentration and excitation intensity. 1 A great example for examination of the described phenomena is Protoporphyrin IX (PpIX), which has been reported to exhibit all three of the above-mentioned RISC reactions, as manifested by DF emission [21][22][23][24]. PpIX is one of the most common photosensitizers that is used in a range or clinical applications, such as fluorescence-guided tumor resection, or photodynamic therapy (PDT) of skin diseases and cancer [25][26][27].…”
Section: Introductionmentioning
confidence: 99%